The Tolerance in Poetry of Antara bin Shaddad Thematic Analysis - Kouyate, Sekou (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2020)
The research aims to read some models of the poet (Antara bin Shaddad" in view of thematic criticism tools, which searches for topics within the literary text, and put them under one principal topic. The researcher used the thematic approach, for categorizing the topics in the selected models, and distinguish the dominant topic among all other sub-themes. Moreover the most important results were:Despite the diversity of the topics of the poem, between the topic of tolerance, injustice, asking for help, and animal complaint, the topic of the tolerance is the main and most important topic, because all other subjects followed it.